Selective visual processing across competition episodes: a theory of task-driven visual attention and working memory - Schneider, Werner X. (The Royal Society, 2013)
The goal of this review is to introduce a theory of task-driven visual attention and working memory (TRAM). Based on a specific biased competition model, the ‘theory of visual attention’ (TVA) and its neural interpretation (NTVA), TRAM introduces the following assumption. First, selective visual processing over time is structured in competition episodes. Within an episode, that is, during its first two phases, a limited number of proto-objects are competitively encoded—modulated by the current task—in activation-based visual working memory (VWM). In processing phase 3, relevant VWM objects are transferred via a short-term consolidation into passive VWM. Second, each time attentional priorities change (e.g. after an eye movement), a new competition episode is initiated. Third, if a phase 3 VWM process (e.g. short-term consolidation) is not finished, whereas a new episode is called, a protective maintenance process allows its completion. After a VWM object change, its protective maintenance process is followed by an encapsulation of the VWM object causing attentional resource costs in trailing competition episodes. Viewed from this perspective, a new explanation of key findings of the attentional blink will be offered. Finally, a new suggestion will be made as to how VWM items might interact with visual search processes.